Dermoscopy of the diverse spectrum of cutaneous tuberculosis in the skin of color - Rashmi Jindal; Payal Chauhan; Sheenam Sethi (Dermatology Practical & Conceptual, 2022)
Introduction: Cutaneous tuberculosis is an uncommon form of tuberculosis, accounting for 1-2% of all forms of extra-pulmonary tuberculosis. Knowledge of the dermoscopy characteristics of different clinical types of cutaneous tuberculosis can help timely diagnosis resulting in better outcomes.